Risk Factors Leading to Anti-TNF Alpha Therapies in Pediatric Severe Uveitis - Osswald, Delphine; Rameau, Anne-Cécile; Terzic, Joëlle; Sordet, Christelle; Bourcier, Tristan; Sauer, Arnaud (Frontiers in Pediatrics, 2022)
Purpose Pediatric uveitis is the leading cause of acquired child blindness, due to unremitting inflammation and long-term steroid exposition. Biotherapies with anti-tumor necrosis factor alpha (anti-TNFα) are effective in controlling inflammation for severe pediatric uveitis in recent studies. Major concern of anti-TNFα prescription is the balance between the severity of the disease and side effects of the drug. The aim of the present study is to describe a cohort of children with severe uveitis and to highlight the risk factors for a pejorative development that led to the prescription of anti-TNFα drugs. Method A retrospective case-control study was carried out on children with uveitis associated with systemic inflammatory disease or idiopathic uveitis, with a minimum follow-up of 5 years. Anti-TNFα-treated patients (case) were studied and compared with patients who were not requiring anti-TNFα (control). Univariate logistic regression analyses were performed to compare both groups and determine the risk factors for anti-TNFα therapy. Results Seventy-three cases of pediatric uveitis were included, 13 cases and 60 controls. The risk factors associated with increased odds of anti-TNFα therapy were initial systemic disorder associated with uveitis [OR = 11.22 (1.37–91.85), p = 0.0241), family history of autoimmune diseases [OR = 9.43 (2.27–39.15), p = 0.0020], uveitis diagnosis before the age of 6 [OR = 4.05 (1.16–14.13), p = 0.0284], eye surgery [OR = 26.22 (2.63–261.77), p = 0.0054], ocular complications at the first slit lamp exam [OR = 67.11 (3.78–1191.69), p = 0.0042], low visual acuity at diagnosis (≥0.3 logMAR) [OR = 11.76 (2.91–47.62), p = 0.0005] and especially low binocular acuity at diagnosis (≥0.3 logMAR) [OR = 8.75 (1.93–39.57), p = 0.0048], panuveitis [OR = 9.17 (2.23–37.60), p = 0.0021], having positive ANA [OR = 3.89 (1.07–14.11), p = 0.0391], and positive HLA B27 [OR = 9.43 (2.27–39.16), p = 0.0020]. Conclusion Those risk factors could be used to establish a new follow-up and treatment schedule for severe uncontrolled uveitis. This could help to better predict the best time to start anti-TNF therapy.